KEWENANGAN HUKUM APARAT KEPOLISIAN PADA PROSES PENEGAKAN ILLEGAL FISHING - Zulfitri Al Azhar, Baginda; Junita Melo, Isye; Darmayanti Putong, Diana (At-Tanwir Law Review, 2025)
Illegal fishing refers to fishing activities that are conducted in violation of the laws and regulations in force in Indonesia. The Talaud Islands Regency, known for its significant marine resource potential, frequently encounters serious challenges related to illegal fishing practices. The prevalence of fisheries-related crimes, particularly illegal fishing in the waters surrounding Talaud, raises important concerns regarding the effectiveness of law enforcement in the region. Law enforcement in the fisheries sector plays a vital and strategic role in supporting the controlled and sustainable development of fisheries, in accordance with the principles of responsible resource management. Therefore, this study aims to examine the legal framework governing police authority in the enforcement of laws against illegal fishing, as well as the practical implementation of criminal law enforcement against illegal fishing in the territorial waters of the Talaud Islands Regency. Using a normative legal research method, this study finds that the authority of the police in addressing illegal fishing is regulated through the Indonesian National Police Law and the Fisheries Law, along with several special mandates provided by statutory regulations and inter-agency coordination mechanisms. However, in practice, the enforcement of criminal law against illegal fishing in Talaud’s territorial waters—despite being conducted through inter-institutional cooperation—still faces numerous challenges that hinder its overall effectiveness.